Ecocultural Control of Natural Energy Resources in Southern Ethiopia - Amborn, Hermann (Aethiopica, 2012)
Dealing with resource problems, energy balance and sustainable climate protection have emerged as subjects of public interest. Indigenous knowledge and concepts, however, are seldom dealt with by western scientists. On the basis of exemplary cases from south-western Ethiopia the interdependence of technical, social and symbolic knowledge and experiences is demonstrated, from which a model can be derived. With the help of the model it can be shown, how, under certain cultural conditions, through controlled mastery of vital resources, a symbiotic relationship between humans and their environment can be developed which does not endanger the particular habitat. The decisive factor in this case is an ethos that places man in a context of space and time which goes beyond his own lifetime and provides a link to past and future generations. Counterexamples show the fragile character of the presented system of relationships.